Determination of Environmental Flow of the Birrís River, Costa Rica - Guzmán-Arias, Isabel (2019)
In Costa Rica, the environmental flow corresponds to 10% of the average river flow. This percentage has lacked of scientific basis in relation to the fluvial conditions suitable for preserving the ecosystems present in the river. Water concessions for the main uses (human, agricultural and hydroelectric) have caused environmental damages, transforming the physical and chemical conditions of the channels. Of the water flow of the Birrís River, 20% is granted for consumptive use as agricultural, human and irrigation production, and the rest is used for hydroelectric generation. Due to the low quality of its waters to date there are no indicator species that makes it impossible to use approaches that take into account ecosystems to generate preference curves. The present work used a hydrological approach to determine the environmental flow of the Birrís River using the flow duration curve methodology. It is based on the analysis of series of climate data obtained for 10 years and series of daily flows from a period of three years. Three outflows of biota and flow were made in three points distributed along the main channel distributed over a period of one year. Finally, the environmental flow was determined based on the flow regime of the average monthly values.